Stochastic Analysis In Mathematical Physics : Proceedings of A Satellite Conference of ICM 2006. - Ben Arous, Gerard; Cruzeiro, Ana Bela; Jan, Yves Le (World Scientific, 2007)
The Steiner tree problem is one of the most important combinatorial optimization problems. It has a long history that can be traced back to the famous mathematician Fermat (1601A-1665). This book studies some of the applications of Steiner tree problems in computer communication networks, which have been discovered and studied extensively in the past ten years. It not only covers some of the most recent developments in Steiner tree problems, but also introduces various combinatorial optimization methods, thus providing a balance between theory and practice.